ANALYSIS OF FACILITY QUALITY AT THE TRADITIONAL MARKET TOURIST ATTRACTION OF KRENENG DENPASAR - Putu Wibby Prasetya (Journal of Innovation Research and Knowledge, 2024)
Kreneng Market in Denpasar City has been formally designated as a Cultural Tourist Attraction (DTW) through regional regulations. However, the rapid growth of modern retail confronts this market with the challenge of declining physical tourism amenities. This study aims to systematically measure and evaluate the quality of physical facilities at Kreneng Market from the tourists' perspective to map out revitalization priorities. Utilizing a quantitative descriptive method, data were collected through structured questionnaires from 100 respondents selected via purposive sampling. Data analysis employed descriptive statistics after the questionnaire instrument was declared valid (Sig. < 0.05) and reliable (Cronbach's Alpha = 0.875). The research results indicate that the overall quality of Kreneng Market's facilities falls into the "Poor" category with a mean score of 2.15. Partially, the aspect of vehicle security in the parking area recorded the highest score (2.30), followed by the physical condition of the building and roof (2.29). Conversely, the market area cleanliness indicator became the most critical point with the lowest score (1.97) due to the duality of its 24-hour operational function, followed by the poor quality of night lighting (2.08), which disrupts the comfort of night-tourism. As a practical implication, this study recommends managerial interventions through three strategic steps: structuring hygiene management based on daily operational shifting, modernizing public toilets with Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) certification, and revitalizing LED lighting in the night culinary zone. Through the integration of these physical amenity improvements, Kreneng Market is expected to shed its slum image and transform into a clean, comfortable, and competitive traditional shopping tourism destination.